From Habit-Forming to Habit-Breaking Availability: Experiences on Electronic Gambling Machine Closures During COVID-19 - Marionneau, Virve; Järvinen-Tassopoulos, Johanna (Frontiers in Psychology, 2022)
Electronic gambling machines (EGMs) are among the most harmful forms of gambling. The structural characteristics of EGMs prolong and reinforce gambling similarly to other habit-forming technologies. In Finland, the wide availability of EGMs in non-casino locations is likely to further reinforce the habit-creating nature of gambling offer by incorporating EGMs into everyday practices. The COVID-19 pandemic changed the landscape of gambling in Finland. The most visible change was the closure of land-based EGMs in non-casino environments, arcades, and the casino in March 2020. Since then, the status of EGMs has varied depending on the pandemic situation. The current qualitative study focuses on how Finnish past-year gamblers experience prolonged EGM closures and occasional re-openings 1 year into the pandemic. The data consist of responses to an online questionnaire eliciting experiences (N = 187) as well as interviews (N = 27, conducted in groups or alone). To aid our analysis, we employ the sociological pragmatist theory of the concept of “habit.” The analysis focuses on gambler experiences on EGM shutdowns and re-openings, and views on whether closures have contributed to abstaining from gambling or to shifting to other gambling products. Policy implications of the results are discussed.